THE NORTH ATLANTIC DIRECTION OF THE REPUBLIC`S OF NORTH MACEDONIA FOREIGN POLICY - Petr, Smirnov (Proceedings of the IX International Scientific Conference "Social Changes in the Global World" – Young researchers 2022, 2022)
After the declaration of independence, the Republic of North Macedonia began to build independent foreign policy, the most important place in which was occupied by relations with the United States and NATO. In the context of the collapse of the bipolar system and instability in the Balkan region, cooperation with Brussels and Washington was of particular importance for the Macedonian republic.Macedonian policy towards the United States and NATO in the first decade of its independent existence was determined by the unstable situation in the region caused by the lack of democratic transit in the FRY. The existence of a threat to national security from the Milosevic regime forced the Macedonian republic to actively cooperate with the Alliance, which was primarily expressed in joining the Partnership for Peace program in 1995.During the conflict of the Macedonian army with an extremist pro-Albanian organization in 2001, the United States and NATO (along with the EU) participated in the settlement process, which led to the signing of the Ohrid Agreements. In the future, the “North Atlantic vector” of Skopje’s foreign policy became clearer, which was explained by the need to resolve the name dispute with Greece. In line with this process, the recognition of the Macedonian republic by the United States under the constitutional name took place, as well as a similar decision by Skopje in relation to Kosovo. With the beginning of the crisis in relations between Russia and the United States in 2013 the movement of most states of the Balkan region (including Macedonia) towards NATO has become more intense, as a result of which the Republic of North Macedonia became a member of the North Atlantic Alliance in 2020.Thus, relations with the United States and NATO currently occupy a key position in the foreign policy of the Republic of North Macedonia in the context of larger processes.